Factors Associated with Completeness of Basic Immunization in Children Under Five in The Working Area of Bangko Jaya Community Health Center - Novita Saragi; Oktavia Dewi; Azzah Rawani (LPPM Universitas Harapan Bangsa, 2024)
The health law states that every child has the right to receive basic immunization in accordance with the provisions. At Bangko Jaya Community Health Center, only 76.7% of children under five received complete basic immunization. This study aims to determine the factors associated with completeness of basic immunization for children under five in the working area of Bangko Jaya Community Health Center, Rokan Hilir Regency. This study uses a qualitative phenomenological research method that explains the reasons for incomplete basic immunization in children under five. This research was conducted from November 27 to December 14, 2023. The informants in this study were parents of children under five, cadres and immunization program holders, parents, and community perceptions of immunization. The informant selection technique was based on availability to be interviewed and adequacy. Based on the results of in-depth interviews with parents of children under five and the community in the working area of Bangko Jaya Community Health Center, the main obstacles to participation in immunization for children under five involve several aspects. [From the results of the residency report, parents of children under five tend to be less active in immunization activities, feel they do not need to return after immunization is complete, or have difficulty attending due to work. Efforts to increase participation involve innovative strategies such as providing rewards to children under five who diligently attend or holding interesting activities at the integrated health service post. On the other hand, public perceptions of immunization are still influenced by fears of vaccine side effects or religious views. From the results of the residency report, it can be concluded that the importance of collaboration with community leaders and village government in changing this perception is a key factor in increasing participation. Thus, a comprehensive approach is needed that involves collaboration between health workers, integrated health service post cadres, community leaders, and village government to design more effective counseling strategies and improve service quality.